2006
DOI: 10.1074/jbc.m510258200
|View full text |Cite
|
Sign up to set email alerts
|

The Farnesoid X Receptor Modulates Adiposity and Peripheral Insulin Sensitivity in Mice

Abstract: The farnesoid X receptor (FXR) is a bile acid (BA)-activated nuclear receptor that plays a major role in the regulation of BA and lipid metabolism. Recently, several studies have suggested a potential role of FXR in the control of hepatic carbohydrate metabolism, but its contribution to the maintenance of peripheral glucose homeostasis remains to be established. FXR-deficient mice display decreased adipose tissue mass, lower serum leptin concentrations, and elevated plasma free fatty acid levels. Glucose and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
445
6
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(491 citation statements)
references
References 39 publications
(44 reference statements)
23
445
6
5
Order By: Relevance
“…In the light of recent findings that bile saltmediated FXR signaling controls liver regeneration and may even control liver size [44], Bsep may move up to a key protein controlling many vital processes in liver. Furthermore, evidence that the bile acid sensor FXR is controlling glucose and lipid metabolism is rapidly accumulating [11,16,58]. Since FXR requires bile salt binding to act to control expression target genes, Bsep may, by controlling bile salt concentration in systemic circulation, become an important control element in body energy and lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of recent findings that bile saltmediated FXR signaling controls liver regeneration and may even control liver size [44], Bsep may move up to a key protein controlling many vital processes in liver. Furthermore, evidence that the bile acid sensor FXR is controlling glucose and lipid metabolism is rapidly accumulating [11,16,58]. Since FXR requires bile salt binding to act to control expression target genes, Bsep may, by controlling bile salt concentration in systemic circulation, become an important control element in body energy and lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…6D, not only OPN expression was Ϸ3-fold higher in FXR Ϫ/Ϫ NKT cells in comparison to WT cells, but, while exposure of WT NKT cells to Con A resulted in a robust induction of OPN mRNA expression ( p Ͻ 0.05 vs untreated), OPN expression was boosted up to 7-fold in FXR Ϫ/Ϫ NKT cells ( p Ͻ 0.01 vs WT cells treated with Con A). To gain insight on the molecular mechanisms involved in OPN regulation by FXR in NKT cells, additional experiments were conducted using a NKT cell hybridoma (the murine V␣14 invt TCR ϩ CD1d-specific T-T hybridoma DN32.D3 (39). By qualitative RT-PCR, Western blot analysis and real-time qRT-PCR, we found that DN32.D3 cells, nonactivated by Con A, express FXR along with the FXR-regulated gene SHP (Fig.…”
Section: Fxr/shp Directly Regulates Opn Gene Expression On Activated mentioning
confidence: 99%
“…Thus, there is circumstantial evidence to link the activity of FXR to the regulation of bile acid synthesis from cholesterol, providing a link between nutrient absorption and regulation of key steps in the intermediate metabolism. In addition, because bile acids might be toxic for the liver, activation of FXR by natural and synthetic ligands has been shown to prevent bile acid-induced liver toxicity in a variety of rodent models (33)(34)(35)(36)(37)(38)(39). The homeostatic function of FXR in the liver is highlighted by the demonstration that mice harboring a disrupted FXR (FXR Ϫ/Ϫ ) develop spontaneously an array of hepatocellular abnormalities including adenomas and carcinomas.…”
mentioning
confidence: 99%
“…Bile acid activation of FXR in the intestine stimulates synthesis of fibroblast growth factor (FGF) 15/19, which is involved in lipid and carbohydrate metabolism. FXR, through its downstream effect on FGF, is important in maintaining normolipidaemia, normoglycaemia, and bile acid homeostasis [9,10] . FGF inhibits CYP7A1 expression, the first step in the conversion of cholesterol to bile acids.…”
Section: Bile Acid-activated Receptorsmentioning
confidence: 99%